UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS VIIA DENGAN MODEL PROBLEM BASED LEARNING DI MTS MUHAMMADIYAH TRUCUK KLATEN TAHUN PELAJARAN 2021/2022 - Sriwiyata (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The purpose of this research was to increase students’ learning at grade VII A through Problem Based Learning (PBL) at MTS Muhammadiyah Trucuk Klaten in the academic year 2021/2022. The method in this study was classroom action research. This classroom action research was conducted at MTS Muhammadiyah Trucuk Klaten. This research was conducted for 6 months starting from March to October 2021. The subjects in this study were 30 students at grade VIA. The steps of action research included planning, implementation, data collection, and reflection on each step for two cycles. The results of the pre-cycle research showed that the average level of students’ activness was 62%. Meanwhile, in the first cycle, the average activeness of students from indicators 1 to 12 reached 74%. In the second cycle, the activeness of students was an average of 73%. Thus, it was concluded that there was an increase in the activeness of students in learning on the material for the formulation and ratification of the 1945 Constitution of the Republic of Indonesia at MTS Muhammadiyah Trucuk Klaten.